PhABC: A Hybrid Artificial Bee Colony Strategy for Pairwise test suite Generation with Constraints Support - Alazzawi, A.K. (Institute of Electrical and Electronics Engineers Inc., 2019)
Software testing becoming significant part of our daily life due to a software-development process that led to increase the components number and the associated time. Due to the financial resources and time constraints, practically exhaustive testing is hopeless. For this reason, numerous researchers have adopted pairwise testing to decrease the exhaustive number of test cases. Pairwise testing is one of a powerful Combinatorial Testing Technique (CTT) that used widely for test data generation. Various existing research works were developed using a meta-heuristic algorithm as a basis for pairwise testing strategies. Supplementing to earlier research work, this paper proposed a new pairwise test suite generation called pairwise hybrid artificial bee colony (PhABC) strategy based on hybridize of an artificial bee colony (ABC) algorithm with a particle swarm optimization (PSO) algorithm. The output of PhABC is a set of promising optimal test set combinations. The results of the experiments showed that PhABC outperformed and yielded better test sets than other existing other research strategies even with the existing constraints. Â© 2019 IEEE.